2021
DOI: 10.1002/jbm.b.34829
|View full text |Cite
|
Sign up to set email alerts
|

Cost effective optimised synthetic surface modification strategies for enhanced control of neuronal cell differentiation and supporting neuronal and Schwann cell viability

Abstract: Enriching a biomaterial surface with specific chemical groups has previously been considered for producing surfaces that influence cell response. Silane layer deposition has previously been shown to control mesenchymal stem cell adhesion and differentiation. However, it has not been used to investigate neuronal or Schwann cell responses in vitro to date. We report on the deposition of aminosilane groups for peripheral neurons and Schwann cells studying two chain lengths: (a) 3‐aminopropyl triethoxysilane (shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(30 citation statements)
references
References 36 publications
(77 reference statements)
0
30
0
Order By: Relevance
“…We previously reported that 11-aminoundecyltriethoxysilane better supported primary neuron, primary Schwann cell, and NG108-15 neuronal cell adhesion, proliferation, viability, and differentiation compared to APTES-modified substrates due to increasing hydrophilicity and surface roughness and decreasing Young's modulus of the substrates due to chain length. [14] In this study, we have successfully modified PCL, an FDA-approved polymer used in peripheral nerve repair, with 11-aminoundecyltriethoxysilane for potential use in nerve tissue engineering applications. [17] The addition of aligned fibers to the lumen of nerve guidance conduits has been shown to improve nerve regeneration and increase axon outgrowth compared to hollow conduits, though distances are not yet comparable with autograft use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that 11-aminoundecyltriethoxysilane better supported primary neuron, primary Schwann cell, and NG108-15 neuronal cell adhesion, proliferation, viability, and differentiation compared to APTES-modified substrates due to increasing hydrophilicity and surface roughness and decreasing Young's modulus of the substrates due to chain length. [14] In this study, we have successfully modified PCL, an FDA-approved polymer used in peripheral nerve repair, with 11-aminoundecyltriethoxysilane for potential use in nerve tissue engineering applications. [17] The addition of aligned fibers to the lumen of nerve guidance conduits has been shown to improve nerve regeneration and increase axon outgrowth compared to hollow conduits, though distances are not yet comparable with autograft use.…”
Section: Discussionmentioning
confidence: 99%
“…[29] The increase in surface roughness when modifying PCL with CL11 is in line with our previous findings, in which CL11 modification of glass increased surface roughness compared to using APTES. [14,26] Modifying PCL fibers with oxygen plasma and CL11 changed the adhesive properties of the PCL fibers. The modifications caused a decrease in adhesiveness and the force recorded between the polymer fiber and the AFM cantilever tip made using silicon nitride.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because NGCs lack associated extracellular matrix tissue, topographical cues, and cellular features that autografts possess [41]. However, a required second surgery, as well as donor site morbidity, is associated with autograft use and so research strategies focus on improving NGCs, such as the inclusion of cellular therapies, surface modifications, improved topography and physical guidance cues, for critical gap injury use [42]. MCL-PHAs, such as P(3HO), exhibit mechanical properties close to that of native nerve tissue, whereas SCL-PHAs exhibit excellent biocompatibility, processability and bioresorption profiles [43].…”
Section: Nerve Conduitsmentioning
confidence: 99%
“…NGCs are typically hollow tubes that connect one end of the nerve to the other [ 142 ]. A scaffold for axonal proliferation, support cells such as stem cells or Schwann cells, growth factors, and an extracellular matrix are the fundamental components of nerve regeneration constructions [ 143 ].…”
Section: Biomedical Applications Of Phamentioning
confidence: 99%